Analisis Independensi Auditor Terhadap Tindakan Kecurangan (Fraud) Pada Audit Laporan Keuangan (International Forum of Researchers and Lecturers, 2024)
This study aims to find out about the analysis of auditor independence towards fraud in financial statement audits. The data used in this study are secondary data derived from journals in previous research, auditor behavior and acts of fraud in financial statement audits. In this study, to obtain journal data collection methods were used. Data collection methods used are descriptive methods, literature studies, and literature. From the results of the evaluation and analysis of the field data that has been carried out, it can be concluded that (1) the auditor should have a good Internal Locus Of Control so that decisions made are not influenced by other external factors, (2) an auditor should not be influenced from differences in work experience between senior auditors and junior auditors, because there were no significant differences in the auditor's ethical behavior in dealing with audit conflict situations, (3) ethical behavior should not link the roles of men and women in society, so that it involves women's abilities in carry out their duties and profession.